PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN DAN ETIKA PROFESI TERHADAP TINGKAT MATERIALITAS AKUNTAN PUBLIK - Natalia, Dessy Agusningtyas; Murni, Siti Asiah (Liability, 2019)
Various attempts to increase income and survive in the face of competition continues to be done by the business processing. One policy that is always taken by the company is to carry out the examination of financial statements by a third party, namely the auditor as an independent party considered. Apublic accountants are required to have sufficient competence, while competence is professionalism, knowledge and professional ethics detecterrors in consideration of materiality levels of public accountants. The purpose of this study was to obtain empirical evidence about the professionalism, knowledge and professional ethics detecterrors in consideration of materiality levels of public accountants. Data obtained from questionnaires filled out by junior to senior accountant who worked in the Public Accountant. Data were analyzed using multiple regression. The results of this study indicate that the professionalism and knowledge detect no significant and negative while professional ethics significant and positive impact. But when tested simultaneously professionalism, knowledge and professional ethics detecterrors significantly and positively influence.